The Role of TikTok Features on Enhancing the Addiction of Content Consumption among Users - Fauzani, Mulia Ramdhan; Utami, Ria; Aeni, Tri (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2025)
The Short-Video Apps (SVA) TikTok is currently one of the most widely used mobile applications. However, there is an increasing trend of social media consumption addiction on a global scale, including addiction to TikTok videos which has implications for reducing the quality and number of meaningful interactions and poses a risk to mental health. Despite recent studies shedding light on TikTok addiction, no detailed explanation has been found regarding the role of TikTok features in the rise of content consumption addiction. This study aims to analyze the explanations provided by previous studies on TikTok content consumption addiction, identify the main features of TikTok for content consumption, and determine the role these features play in increasing content consumption addiction. Through observation and a review of the relevant literature, relevant studies revealed that TikTok addiction is an outcome of the process of creating flow experiences for users on the platform. Despite the potential for generating content consumption addiction implications, the creation of flow experiences is important for TikTok, as the company implements an attention economy business model. TikTok offers a variety of features designed to enhance user engagement and prolong content consumption, including the video viewing page, search column, and push notifications. These three features contribute to the creation of a fluid experience that encourages the consumption of addictive content. The video viewing page plays a vital role in this experience, as it provides all four aspects of system quality that can sustain user attention. Meanwhile, the Search Column and the Notification feature serve a more limited function, as they lack the flexibility and usability of the Watch Video Page. Aplikasi Short-Video Apps (SVA) TikTok merupakan salah satu aplikasi paling populer saat ini. Namun, terjadi peningkatan tren kecanduan konsumsi media sosial dalam skala global, termasuk kecanduan mengkonsumsi video TikTok yang berimplikasi pada penurunan kualitas dan jumlah interaksi bermakna serta risiko kesehatan mental. Meskipun penelitian-penelitian terkini telah menjelaskan mengenai kecanduan TikTok, belum ditemukan penjelasan detail mengenai peran fitur TikTok dalam peningkatan kecanduan konsumsi konten. Penelitian ini bertujuan untuk menganalisis bagaimana penelitian-penelitian menjelaskan kecanduan konsumsi konten TikTok; apa saja fitur-fitur utama TikTok untuk menkonsumsi konten; dan bagaimana fitur-fitur tersebut berperan dalam meningkatkan kecanduan konsumsi konten. Melalui observasi dan studi literatur, penelitian-penelitian menunjukkan bahwa kecanduan TikTok merupakan luaran dari proses terciptanya flow experience yang diberikan oleh platform kepada para pengguna. Terciptanya flow experiences, meskipun berisiko menghasilkan implikasi kecanduan konsumsi konten, penting bagi TikTok, karena perusahaan ini menerapkan model bisnis ekonomi perhatian atau attention economy. TikTok menawarkan berbagai fitur untuk meningkatkan keterlibatan pengguna dan memperpanjang durasi konsumsi konten, di antaranya Laman Menonton Video, Kolom Pencarian, dan Notifikasi Push. Ketiga fitur tersebut memiliki peran dalam menciptakan flow experience yang berujung pada kecanduan konsumsi konten. Laman Menonton Video berperan vital karena memberikan keempat aspek kualitas sistem yang dapat mempertahankan perhatian pengguna. Sementara peran fitur Kolom Pencarian dan Notifikasi lebih sempit karena aspek fleksibilitas dan ease of use tidak sebaik Laman Menonton Video.